Short and Long Run Relationship Between Value of Total Stock Exchange Transaction and Key Macroeconomic Variables in Nigeria. A Cointegration Approach - Akpan, Sunday B.; Inya-Agha, Chukwu E.; Aya, Ebirigor A.; Udo, Friday J.; Akpan, Obot D. (Richtmann Publishing, 2012)
The study analyzed the short run and long run influenced of some macroeconomic variables on ttotal stocktransactions in the Nigerian stock exchange market. Unit root test (Augmented Dicker Fuller test) conducted on the data showsthat all variables are integrated of order one. The short-run and long-run elasticities of total stock transaction with respect tosome key macro-economic variables were determined using the techniques of co-integration and error correction estimation.The empirical results reveal that coefficients of industrial capacity utilization rate, domestic savings, external reserves, total valueof import and lending rate of commercial Banks are significant in the long run. Whereas the coefficients of external debt,domestic savings, total import, per capita real GDP; industrial capacity utilization and index of agricultural production weresignificant in the short run. The result calls for a policy package that should focused on stabilization of the real and monetarypolicy variables in the Nigerian economy. Also, institutional and operational reforms in the country’s capital market are inevitablein a bit to increase the stock exchange market’s efficiency.